Microsoft System Center 2012 Orchestrator cookbook : automate mission-critical tasks with this practical, real-world guide to System Center 2012 Orchestrator /: automate mission-critical tasks with this practical, real-world guide to System Center 2012 Orchestrator. (2013) - Erskine, Samuel; Baumgarten, Andreas; Beaumont, Steve
No abstract available